CSR and Profitability as Determinants of Firm Value: Evidence from Sri-Kehati Index - Ono Tarsono; Maya Mustika; Fasya Nabila Salim; Dwi Windu Suryono (SAN Scientific, 2026)
This study aims to investigate the impact of Corporate Social Responsibility (CSR) and profitability on firm value among companies listed on the Sri-Kehati Index of the Indonesia Stock Exchange (IDX) during the 2021–2024 period. A descriptive quantitative research design was applied using panel data analysis with EViews 12. The population consisted of firms listed on the Sri-Kehati Index, with purposive sampling selecting 11 companies, resulting in 44 firm-year observations. Secondary data were collected through documentation from the official IDX website (www.idx.co.id). The results reveal that CSR has a negative and significant effect on firm value, while Return on Assets (ROA) and Return on Investment (ROI) do not have a significant effect. These findings suggest that while CSR initiatives significantly shape firm value, profitability indicators such as ROA and ROI may not directly drive market valuation in Sri-Kehati Index firms.